2002
DOI: 10.1046/j.1537-2995.2002.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

RBC T activation and hemolysis in a neonatal intensive care population: implications for transfusion practice

Abstract: T variant activation of RBCs occurs in healthy neonates as well as in infants with NEC and sepsis, but T activation appears rare. Transfusion- associated hemolysis was not seen. The provision of specially prepared blood components for infants with NEC is unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Although T activation has been detected on the RBCs of up to 30% of neonates who have NEC, clinical haemolysis rarely is observed. 15 , 16 Four percent of the patients had haemosiderin and haematuria but without clinical evidence of worsening haemolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Although T activation has been detected on the RBCs of up to 30% of neonates who have NEC, clinical haemolysis rarely is observed. 15 , 16 Four percent of the patients had haemosiderin and haematuria but without clinical evidence of worsening haemolysis.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have shown an association of NEC with activation of the Thomsen-Friedenreich cryptic T antigen (T-activation) on RBCs, causing low-grade hemolysis and anemia in multi-transfused patients who have previously received blood from adult donors carrying anti-T antibodies (27). The pathophysiological significance of T-activation in NEC remains unresolved (28), yet a finite possibility remains that some patients with “transfusion-associated” NEC could have had a low-grade smoldering illness prior to the transfusion. Growing preterm infants who are anemic but otherwise stable are usually monitored with an expectation of spontaneous improvement in hematocrits.…”
Section: Discussionmentioning
confidence: 99%
“…T-activation can cause hemolysis and anemia in multi-transfused patients who have previously received adult blood containing anti-T antibodies (26, 27). Studies show considerable variation in the frequency of T-activation in NEC, ranging from rare occurrences to up to a third of all patients (6, 28). T-activation is associated with increased morbidity and mortality in NEC.…”
Section: Anemiamentioning
confidence: 99%